ANALISIS PENOLAKAN PERMOHONAN DISPENSASI KAWIN DI PENGADILAN AGAMA WATES : (Studi Terhadap Perkara nomor 39/Pdt.P/2018/PA. Wts) - Mutasir; Hendri Kroniko; Akmal Abdul Munir; Ismi Lathifatul Hilmi; Armi Agustar (Jurnal Akademika Kajian Ilmu-Ilmu Sosial, Humaniora Dan Agama, 2023)
Abstract This article is motivated by the rejection by the Wates Religious Court of the application for marriage dispensation based on the Judge's view of the conditions of the applicant and the bride and groom to be married. The purpose of this article is to find out the reasons for the Judge's refusal and analyze it with child protection theory. This research is qualitative by using a case study approach in court case number 39/Pdt.P/2018/PA. Wts. The result of this analysis is that granting and rejecting applications for marriage dispensation is not an easy thing for the Judges. The panel of judges makes full efforts to ijtihad to find the best result for the child. The judge considers the long-term benefits of marriage. They emphasize that the implementation of marriage is not difficult but requires effort to maintain it. By considering the long-term benefits and understanding that running a marriage is hard, couples need to prove that each has an understanding and readiness both mentally, economically, and psychologically. Keywords: Marriage Dispensation, Child Marriage, Child Protection.